Auditing scholarly journals published in Malaysia and assessing their visibility - Awang Ngah, Zainab; S.A., Sanni; N.N., Edzan; Koh, A.P. (Malaysian Journal of Library and Information Science, 2017)
Zainab, A. N., Sanni, S. A., Edzan, N. N., & Koh, A. P. (2012). Auditing scholarly journals published in Malaysia and assessing their visibility.Â Malaysian Journal of Library & Information Science,Â Vol.17, no. 1: 65-92. The problem with the identification of Malaysian scholarly journals lies in the lack of a current andÂ complete listing of journals published in Malaysia. As a result, librarians are deprived of a tool thatÂ can be used for journal selection and identification of gaps in their serials collection. This studyÂ describes the audit carried out on scholarly journals, with the objectives (a) to trace andÂ characterized scholarly journal titles published in Malaysia, and (b) to determine their visibility inÂ international and national indexing databases. A total of 464 titles were traced and their yearlyÂ trends, publisher and publishing characteristics, bibliometrics and indexation in national,Â international and subject-based indexes were described.